GIS-based multi-criteria approach for block level drought hazard mapping in the Purulia District, West Bengal, India - Kajal Kumar Mandal; Snehashis Alam; Toushif Jaman; Mohan Kumar Bera (Discover Environment, 2025)
Abstract Drought is a catastrophic event that is happening more frequently and has a serious effect on socio-economic aspects. A drought hazard zonation map is essential to mitigate the drought hazards. Therefore, the main objective of this study is to prepare a drought hazard map for Purulia district, West Bengal, India, using Multi Influencing Factor (MIF) analysis and geospatial methods. We evaluated several critical parameters that affect drought, such as land surface temperature (LST), normalized difference vegetation index (NDVI), precipitation, drainage density, soil, slope, and geomorphology. Thematic maps were prepared and compiled for each parameter through overlay analysis in ArcGIS version 10.8.2. The results show that 12.3% of the Purulia district is under extreme drought (9 blocks), 53.7% severe drought (6 blocks), 31.5% moderate drought (5 blocks), and 2.6% abnormal dry. The district-level drought hazard map was also verified by using the ROC curve, finding it to be accurate. These results can be helpful for decision-makers and government departments working in agricultural planning, disaster management, rural development, and land degradation management at the Purulia district, West Bengal.